الاستطراد والنقد التلميحيّ في أمالي (اليزيديّ- القالّي- ابن الشجريّ) - يعقوب, عبد الكريم; ديّوب, هيفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
النقد التلميحيّ واحدٌ من الأسباب والدوافع التي دعت أصحاب الأمالي إلى الاستطراد, بفعل تنوّع الحياة دينيّاً, واجتماعيّاً, وسياسيّاً. وقد انعكس هذا التنوّع على أساليب التعبير نظراً لاختلاف المشارب المذهبيّة, وتباين المستويات الاجتماعية, وتعدّد التيّارات السياسيّة؛ فقد برزت حريّة التعبير حيناً, لكن غير قليل من الخوف والحذر كان يلازم أهل العلم والمعرفة, فاتخذوا أسلوب الاستطراد مطيّةً لهم, استطاعوا من خلاله أن يبوحوا بأفكار لم يكن التصريح بها ممكناً. والبحث يعالج هذا الأسلوب التعبيري, لدى ثلاثةٍ من أصحاب الأمالي؛ هم: اليزيديّ (310هـ) وأبو علي القاليّ (356هـ), وابن الشجريّ (542هـ), وجاء هذا الاختيار لأن هؤلاء مثّلوا تيّارات ومذاهب متباينة, في مراحل زمنيّة متتالية, ومتباعدة. Implicit criticism is one of the reasons and motives that have driven Al-Amali people to digress because of the religious, social, and political variety of life reflected in terms of expression the difference in religious creeds, the difference of social classes, and the variation of political doctrines. The freedom of expression has sometimes appeared, but a bit of fear and worry has accompanied people of science and knowledge. So they have resorted to digression as a technique they could use to express the inexpressible. This research deals with the expressive style used by three of Al-Amali people: Alyazidi (310 A.H.), Abou Ali Alkali (356 A.H.), and Ibn Al-Shajri (542 A.H.). This choice has come into play because these three have represented different trends and styles in consecutive and remote periods of time.